Investigating the Impact of Consensus Algorithm on Scalability in Blockchain Systems - Kashif Mehboob Khan; Muhammad Abdullah Hayat; Rana Muhammad Ibrahim (Sir Syed University Research Journal of Engineering and Technology)
In the current era, blockchain has emerged as one the best and promising technology. All the cryptocurrencies have also gained a lot of popularity around the globe which are based on blockchain technology. Blockchain provides a distributed architecture, in which transactions are verified by different validators using different algorithms and then are stored in distributed ledger. The verification of transactions is done using consensus algorithms which verifies that incoming transaction is correct and reliable by different distributed nodes working in a peer-to-peer network. Consensus algorithms ensure the integrity and security of blockchain. There are various types of consensus algorithms used in blockchain technology which are used depending on the architecture and usage, some of the consensus algorithms are Proof of Work (PoW), Proof of Stake (PoS) etc. The Proof of Work algorithm is most widely used across the globe by the community. It is used by many popular cryptocurrency networks like Litecoin and Bitcoin. It requires larger computation power while verifying transactions. The selection of a consensus algorithm is one the most important parts of blockchain, as the consensus mechanism is considered to be the core of a network. It is easier to predict and guarantee the security, reliability, fault tolerance, and recoverability of the system if the correct consensus protocol is selected. A single algorithm can never fulfill all the requirements, there is always a tradeoff in the selection of consensus algorithms. Therefore, it is very important to select the best suited consensus algorithm for the network as the consensus mechanism validates transactions without any third-party platform and prevents malicious activities in the network. This paper investigates the comparison among types of consensus algorithms and their effectiveness and viability.